A novel CACNA1S gene variant in a child with hypokalemic periodic paralysis: a case report and literature review - Wen Zhou; Peilin Zhao; Jian Gao; Yunjian Zhang (BMC Pediatrics, 2023)
Abstract Background The CACNA1S gene encodes the alpha 1 S-subunit of the voltage-gated calcium channel, which is primarily expressed in the skeletal muscle cells. Pathogenic variants of CACNA1S can cause hypokalemic periodic paralysis (HypoPP), malignant hyperthermia susceptibility, and congenital myopathy. We aimed to study the clinical and molecular features of a male child with a CACNA1S variant and depict the molecular sub-regional characteristics of different phenotypes associated with CACNA1S variants. Case presentation We presented a case of HypoPP with recurrent muscle weakness and hypokalemia. Genetic analyses of the family members revealed that the proband had a novel c.497 C > A (p.Ala166Asp) variant of CACNA1S, which was inherited from his father. The diagnosis of HypoPP was established in the proband as he met the consensus diagnostic criteria. The patient and his parents were informed to avoid the classical triggers of HypoPP. The attacks of the patient are prevented by lifestyle changes and nutritional counseling. We also showed the molecular sub-regional location of the variants of CACNA1S which was associated with different phenotypes. Conclusions Our results identified a new variant of CACNA1S and expanded the spectrum of variants associated with HypoPP. Early genetic diagnosis can help avoid diagnostic delays, perform genetic counseling, provide proper treatment, and reduce morbidity and mortality.